2012
DOI: 10.1038/ncomms1691
|View full text |Cite
|
Sign up to set email alerts
|

Broadband omnidirectional antireflection coating based on subwavelength surface Mie resonators

Abstract: Reflection is a natural phenomenon that occurs when light passes the interface between materials with different refractive index. In many applications, such as solar cells or photodetectors, reflection is an unwanted loss process. Many ways to reduce reflection from a substrate have been investigated so far, including dielectric interference coatings, surface texturing, adiabatic index matching and scattering from plasmonic nanoparticles. Here we present an entirely new concept that suppresses the reflection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
672
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 777 publications
(709 citation statements)
references
References 32 publications
19
672
2
5
Order By: Relevance
“…47,48 In the liquid phase the Ga behaves as a Drude metal ( Figure 1D) and continues to support plasmonic resonances throughout the near-infrared (NIR). When solid, Ga has a refractive index of n > 5 in the NIR and may support geometric resonances that are strongly damped by interband absorption.…”
Section: Articlementioning
confidence: 99%
“…47,48 In the liquid phase the Ga behaves as a Drude metal ( Figure 1D) and continues to support plasmonic resonances throughout the near-infrared (NIR). When solid, Ga has a refractive index of n > 5 in the NIR and may support geometric resonances that are strongly damped by interband absorption.…”
Section: Articlementioning
confidence: 99%
“…Efficient anti-reflection coatings (AR) have been intensively studied with many different approaches having been explored for this purpose [1][2][3] , such as multi-layered thinfilms 4,5 , graded index matching via surface texturing with micro-and nano-structures [6][7][8][9][10][11] , plasmonic metasurfaces [12][13][14] and more recently, metasurfaces [15][16][17][18][19][20][21] based on ordered arrays of sub-micrometric dielectric antennas (dielectric Mie resonators [22][23][24][25][26][27][28] ). Depending on the application of the AR different aspects (lowest value of the total reflectance, broad spectral range, broad acceptance angle, transparency or light trapping) determine the optimal features and fabrication method.…”
Section: Introductionmentioning
confidence: 99%
“…Though photovoltaic sun tracking system is effective to solve the problem induced by the changed Ξ, it is costly and difficult to work precisely for more than 20–25 years of module lifetime 1. In recent years, there are lots of reports demonstrating that Si nanostructures possess outstanding broadband and omnidirectional antireflection ability, which are promising to be adopted in solar cells to form omnidirectional solar cells for enhancing electric energy output over broad Ξ 2, 3, 4, 5, 6, 7, 8, 9. For example, Spinelli et al2 have reported that Si nanocylinder arrays can effectively suppress reflection over the wide Ξ of 0°–60°.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there are lots of reports demonstrating that Si nanostructures possess outstanding broadband and omnidirectional antireflection ability, which are promising to be adopted in solar cells to form omnidirectional solar cells for enhancing electric energy output over broad Ξ 2, 3, 4, 5, 6, 7, 8, 9. For example, Spinelli et al2 have reported that Si nanocylinder arrays can effectively suppress reflection over the wide Ξ of 0°–60°. Savin et al6 even demonstrated that Si nanopillars textured solar cell brings 3% higher in daily energy production as compared to the conventional Si micropyramids (SiMPs)‐textured solar cell, which benefits from its better angular acceptance.…”
Section: Introductionmentioning
confidence: 99%